2012
DOI: 10.1073/pnas.1205573109
|View full text |Cite
|
Sign up to set email alerts
|

Genetic activation of BK currents in vivo generates bidirectional effects on neuronal excitability

Abstract: Large-conductance calcium-activated potassium channels (BK) are potent negative regulators of excitability in neurons and muscle, and increasing BK current is a novel therapeutic strategy for neuroand cardioprotection, disorders of smooth muscle hyperactivity, and several psychiatric diseases. However, in some neurons, enhanced BK current is linked with seizures and paradoxical increases in excitability, potentially complicating the clinical use of agonists. The mechanisms that switch BK influence from inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(94 citation statements)
references
References 40 publications
(74 reference statements)
0
93
1
Order By: Relevance
“…In some studies, BK channels have been shown to increase, rather than decrease, AP frequency (Brenner et al 2005;Gu et al 2007;Jaffe et al 2011;Lovell and McCobb 2001;MartinezEspinosa et al 2014;Montgomery et al 2012;Shruti et al 2008). Given that BK channels are activated by specific calcium sources, this suggests that some calcium channels' effects on excitability may be partly mediated by activation of proexcitatory BK channels.…”
Section: Given Their Broad Expression These Findings May Be Relevantmentioning
confidence: 99%
“…In some studies, BK channels have been shown to increase, rather than decrease, AP frequency (Brenner et al 2005;Gu et al 2007;Jaffe et al 2011;Lovell and McCobb 2001;MartinezEspinosa et al 2014;Montgomery et al 2012;Shruti et al 2008). Given that BK channels are activated by specific calcium sources, this suggests that some calcium channels' effects on excitability may be partly mediated by activation of proexcitatory BK channels.…”
Section: Given Their Broad Expression These Findings May Be Relevantmentioning
confidence: 99%
“…A study in which BK currents were inhibited with iberiotoxin suggests that this current may contribute 40% of the afterhyperpolarization that occurs after an action potential in the SCN (Cloues and Sather 2003). Blocking the BK current (iberiotoxin) can reduce daytime peak firing rate in at least some SCN neurons (Pitts et al 2006) and genetic manipulation of the BK channel also impacts daytime firing frequency (Montgomery and Meredith 2012;Montgomery et al 2013). Recent work has found that inactivating BK currents predominate during the day in the SCN.…”
Section: Frequency Modulationmentioning
confidence: 99%
“…This increased sensitivity may also be influenced by other factors such as a change in light input to the SCN in Tg-BK R207Q mice, since Per1 is expressed in the retina (70), or developmental differences. The light-induced phase shifts normally transduced through Per1-mediated increases in firing (2,31,60,69) (45). However, those mice were expected to have an inverted circadian phase with strong diurnal behavioral activity, stemming from Tg-BK…”
Section: Subjective Daymentioning
confidence: 99%
“…5, B and E). In addition, although some neurons increased their firing (45) Decreased circadian amplitude in the SCN circuit of Tg-BK R207Q mice. To assess how these changes in daytime excitability impacted rhythmicity of the SCN circuit, we performed long-term multielectrode array recordings from organotypic SCN cultures (Fig.…”
mentioning
confidence: 99%